2016
DOI: 10.1186/s12888-016-0922-6
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide population-based cohort study of psychiatric disorders in individuals with Ehlers–Danlos syndrome or hypermobility syndrome and their siblings

Abstract: BackgroundTo assess the risk of psychiatric disorders in Ehlers-Danlos syndrome (EDS) and hypermobility syndrome.MethodsNationwide population-based matched cohort study. EDS, hypermobility syndrome and psychiatric disorders were identified through Swedish national registries. Individuals with EDS (n = 1,771) were matched with comparison individuals (n = 17,710). Further, siblings to individuals with EDS who did not have an EDS diagnosis themselves were compared with matched comparison siblings. Using condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 29 publications
3
99
0
4
Order By: Relevance
“…Genes coding for extracellular matrix could play a crucial part. The findings by Cederlöf et al, 24 an increased risk of psychiatric disorders not only in individuals diagnosed with EDS but also in their unaffected siblings, support a common genetic component. In most EDS subtypes a pathogenic basis, such as genes involved in collagen synthesis, has been identified, but for hEDS, the genetic aetiology remains unclear.…”
Section: Psychiatric Manifestations As Part Of a Systemic Disordermentioning
confidence: 82%
“…Genes coding for extracellular matrix could play a crucial part. The findings by Cederlöf et al, 24 an increased risk of psychiatric disorders not only in individuals diagnosed with EDS but also in their unaffected siblings, support a common genetic component. In most EDS subtypes a pathogenic basis, such as genes involved in collagen synthesis, has been identified, but for hEDS, the genetic aetiology remains unclear.…”
Section: Psychiatric Manifestations As Part Of a Systemic Disordermentioning
confidence: 82%
“…A systematic review has demonstrated that compared with their non‐affected peers, adults with JHS/hEDS have greater risk of anxiety, depression and panic disorders [Smith et al, ]. A nationwide population‐based cohort study showed a high incidence of psychiatric disorders including anxiety, depression, attention deficit hyperactivity disorder, and autism spectrum disorder in the JHS/hEDS patient population [Cederlöf et al, ].…”
Section: Jhs/eds‐ht In Adulthoodmentioning
confidence: 99%
“…Pain might manifest from the reduced collagen deposition in the skin, ligaments, tendons, joints, and bones. There is a growing body of literature which suggests a possible association between connective tissue disorders, such as EDS, and symptoms of autism or psychiatric disorders 16, 17, 18, 19. It has further been suggested that intense pain may contribute to the emotional burden of the disorder and that psychiatric features may be secondary to EDS 20, 21, 22.…”
Section: Discussionmentioning
confidence: 99%